2023
DOI: 10.5435/jaaosglobal-d-22-00148
|View full text |Cite
|
Sign up to set email alerts
|

Limb Injuries and Disability in the Southwest Region of Cameroon

Abstract: Introduction:Extremity injuries are a leading cause of morbidity in low- and middle-income countries (LMICs), often resulting in marked short-term and long-term disabilities. Most of the existing knowledge on these injuries originates from hospital-based studies; however, poor access to health care in LMICs limits these data because of inherent selection bias. This subanalysis of a larger population-level cross-sectional study in the Southwest Region of Cameroon aims to determine patterns of limb injury, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These findings align with similar studies conducted in different countries, such as the study by M. Post et al in 2008, which validated the IMPACT-S tool. Ahmed Nour et al (2023) conducted a study in Cameroon and found that more than 39% of patients with limb injuries experienced difficulties with activities of daily living ( 28 , 53 ).These findings emphasize the need to improve rehabilitation services from the early stages of post-road traffic injuries to address the limitations in activities and promote better social integration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with similar studies conducted in different countries, such as the study by M. Post et al in 2008, which validated the IMPACT-S tool. Ahmed Nour et al (2023) conducted a study in Cameroon and found that more than 39% of patients with limb injuries experienced difficulties with activities of daily living ( 28 , 53 ).These findings emphasize the need to improve rehabilitation services from the early stages of post-road traffic injuries to address the limitations in activities and promote better social integration.…”
Section: Discussionmentioning
confidence: 99%